Test of Antibacterial Activity of Star Fruit Leaf Ethanol Extract (Averrhoa bilimbi linn) Against the Growth of Propionibacterium acnes - Mory, Ogy Rya; Rini, Desi Indria; Nurina, Rr. Listyawati; Manongga, Fidriati Olivia (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Treatment of Propionibacterium acnes infection can use antibiotics, but the use of antibiotics in the wrong dosage can trigger antibiotic resistance. The development of natural antibacterial research with herbal plant ingredients is one alternative to reduce the incidence of resistance. One of the plants used is star fruit leaf (Averrhoa bilimbi linn). This research aims to determine the antibacterial activity of ethanol extract of star fruit leaf (Averrhoa bilimbi linn) against the growth of Propionibacterium acnes. This research used a true experimental design research type with a post-test only control group design. This research used star fruit leaf extract which is macerated using 70% ethanol solvent and evaporated until a thick extract is obtained. Testing of antibacterial activity using the disc diffusion method (Kirby-Bauer) against the bacteria Propionibacterium acnes. The analysis used is the One Way Anova statistical test. Star fruit leaf extract contains alkaloid compounds, tannins, saponins, flavonoids, and steroids. The test results show that the average diameter of the inhibition zone formed by each sample was at a concentration of 100% of 17,07 mm, a concentration of 50% of 15,21 mm, a concentration of 25% of 14,16 mm, a concentration of 12,5% of 12,86 mm, a concentration of 6,25% of 12,08 mm, a concentration of 3,125% of 10,58 mm and a concentration of 1,56% of 9,16 mm. Star fruit leaf extract (Averrhoa bilimbi linn) has antibacterial activity against the growth of Propionibacterium acnes.